Congenital sick sinus syndrome with breath holding and severe syncope episodes during infancy: a case report - Karagöz, Tevfik; Çeliker, Alpay; Özer, Sema; Özme, Şencan; Saraçlar, Muhsin (The Turkish Journal of Pediatrics, 2000)
Sick sinus syndrome is a rare cause of bradycardia in children without structural heart disease. A case of profound sinus bradycardia, sinus arrest with junctional escape, and pauses in a two-year-old infant with breath-holding and syncope episodes is presented. As a result of these clinical symptoms and electrocardiographic findings, the patient with sick sinus syndrome underwent implantation of transvenous ventricular pacemaker. He has been well and asymptomatic since the insertion of the pacemaker. In the differential diagnosis of an infant with breath-holding and syncope episodes, when these symptoms in particular cannot be explained by other common reasons, sick sinus syndrome should be kept in mind. This case also illustrates the importance of electrocardiographic studies for the diagnosis.